Armored probiotics for oral delivery - Xinyuan Yang; Chong Wang; Qiao Wang; Zhuohao Zhang; Weimin Nie; Luoran Shang (Smart Medicine, 2023)
Abstract As a kind of intestinal flora regulator, probiotics show great potential in the treatment of many diseases. However, orally delivered probiotics are often vulnerable to unfriendly gastrointestinal environments, resulting in a low survival rate and decreased therapeutic efficacy. Decorating or encapsulating probiotics with functional biomaterials has become a facile yet useful strategy, and probiotics can be given different functions by wearing different armors. This review systematically discusses the challenges faced by oral probiotics and the research progress of armored probiotics delivery systems. We focus on how various functional armors help probiotics overcome different obstacles and achieve efficient delivery. We also introduce the applications of armor probiotics in disease treatment and analyze the future trends of developing advanced probiotics‐based therapies.